Bus use in a developing world city: Implications for the health and well-being of older passengers. Issue 2 (June 2015) - Aceves-González, Carlos; Cook, Sharon; May, Andrew
Abstract The aim of this article is to investigate the implications of bus use on the health and well-being of older passengers in a developing world city. Two complementary methods were used. Twenty-six participants aged 60 and over in Guadalajara, Mexico took part in four focus groups to identify the door-to-door elements of the bus service that impose difficulty in terms of accessing and using it, and their impact on the perceived or actual safety, usability and comfort of older passengers. The second part of the study comprised real time observation of 144 older passengers, to investigate the relationship between the characteristics of the bus service and the observed behaviour of older passengers. The results show that issues such as driver behaviour, features of bus design, crowded buses, pedestrian infrastructure and other passengers׳ behaviour present difficulty to older passengers who need or want to use the bus service. The existence of these issues presents serious implications for older users in terms of perceived or actual safety, usability and comfort. Given the importance of the role of public transport, the overall conclusion is that there is an urgent need for further improvement of bus services to maintain and promote the health and well-being of older people.